Tingkat Serangan Spodoptera frugiperda L pada Tanaman Jagung di Desa Batu Belang Dua, Kecamatan Muaradua - Arsi, Arsi; Rahmi, Fadhila; Oclara, Elsa Chendy; Pratiwi, Yuliza Adhe; Apriyanto, Dimas; Indrajaya, Tri Aji; Alamsyah Alrifqi, Muhammad (Seminar Nasional Lahan Suboptimal, 2023)
Arsi, A., Rahmi, F., Oclara, E.C., Pratiwi, Y.A., Apriyanto, D., Indrajaya, T.A., & Alrifqi, M.A. (2023). Spodoptera frugiperda attack level on corn plants in Batu Belang Dua Village, Muaradua Distric. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023.  (pp. 275–284). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Corn (Zea mays L) is one of the food crops and the main source of income for Indonesian people, especially in South Sumatra, however, people's income has decreased due to a significant Spodoptera frugiperda attack. This research aimed to determine the percentage intensity of Spodoptera frugiperda pest attacks in Batu Belang Dua village. The research method used in this research is the survey method through direct observation in the field. The data collected is primary data in the form of direct observation of symptoms in the field and secondary data obtained from farmer interviews. The results obtained from five corn farmers were of productive age, the farmers ranged in age from 30 years to 50 years with a land area of 1 ha. The highest Spodoptera frugiperda L. attack was on land 3 owned by Mr. Ahyar with an average of 16.43% and the lowest was on land 2 owned by Kartini with an average of 9.92%. So, the intensity of Spodoptera frugiperda attacks in Batu Belang Dua village showed that the highest attack was on land 3 belonging to Mr. Ahyar with an average of 16.43%, while the lowest attack was on land 2 belonging to Mrs. Kartini with an average of 9.92%. Therefore, farmers in Batu Belang Dua village must pay attention to the level of Spodoptera frugiperda pest attacking corn crops so that they do not experience very high economic losses.